Man in the “Points of Intensity”: Garden as a Space of Self- Identification - Brazgovskaya, Elena (Respectus Philologicus, 2014)
The article deals with the issue of semiotic and cognitive potential of a garden as a compositional form (“Ogrody” by Jarosław Iwaszkiewicz). Silva rerum, florilegia, hortus act as its genre presupposition in European artistic tradition. We define the semiotic potential of a “garden” through the system of symbolic meanings: garden as a collection, locus amoenus, sphere of potentiality or ordering, garden as a memory space, intellectual space, etc. The garden via a compositional form of this text and the space of thought functions as an iconic sign of memory. Each object of the past, being replaced by a sign, receives localization in our memory and becomes a “text”. This allows us “to read” the past in the absence of an immediate reception. Garden acquires the properties of textuality and a semiotic object. Hence Iwaszkiewicz considers six gardens in “Ogrody” as a model of his life. Memory is a nonlinear space. Therefore, transitions between gardens are only arbitrary, associative. At the same time garden as a compositional form becomes the cognitive tool of identity. Topology of this memory space (configuration of people, books, music, which become signs) is the cognitive map of the “self (selfhood, selfness). The self-referent structures create the illusion: I (the one who writes) is combined with that person from the past (also I), which he recalls. Nonetheless, all narratives about selfhood are only “the map, but not a territory” (A. Korzybski).
Keywords: Jarosław Iwaszkiewicz; Self-Identity; Semiotics of Garden; Representation; Iconic Image; Art Form as a Cognitive Map